Sexual Abuse Disclosure Mediates the Effect of an Abuse Prevention Program on Substantiation. (May 2020) - Elfreich, Molly R.; Stevenson, Margaret C.; Sisson, Crystal; Winstead, Alexandria P.; Parmenter, Katelyn M.
Although abuse prevention programs have proliferated, little research has explored the direct effects of such programs on actual child sexual abuse disclosure rates, and no research has explored the effects of such programs on child sexual abuse substantiation. Employing a quasi-experimental design, the present research reflects an exploration of the effects of exposure to the Think First and Stay Safe™ abuse prevention program on abuse disclosure rates of 319 children who underwent a child forensic interview within 2015–2018 in a Midwestern child advocacy center. Supporting our mediational hypotheses, children exposed (vs. not exposed) to the Think First and Stay Safe™ program were significantly more likely to disclose abuse during the forensic interview, which in turn predicted significantly increased abuse substantiation likelihood.